Effective immunotherapy of cancer in MUC1-transgenic mice using clonal cytotoxic T lymphocytes directed against an immunodominant MUC1 epitope - Heukamp, Lukas C; van Hall, Thorbald; Ossendorp, Ferry; Burchell, Joy M; Melief, Cornelis J M; Taylor-Papadimitriou, Joyce; Offringa, Rienk (Journal of immunotherapy (1997), 2002)
The tumor-associated autoantigen MUCI is intensively studied as a potential target for antigen-specific immunotherapy of cancer. Previous reports concerning experiments in preclinical murine tumor models have provided evidence supporting the feasibility of this approach. However, such studies have not been performed with clonal cytotoxic T lymphocyte populations displaying a highly defined MUC1 specificity. The authors demonstrate that the immunodominant MUC1-specific cytotoxic T lymphocyte response in C57BL/6 mice is directed against an H-2Kb-restricted epitope, MUC1(19-27), which is derived from the N-terminal signal sequence of the MUC1 protein. Processing of this epitope was independent of transporter of antigen presentation and proteasome function. Importantly, successful immunotherapy of MUC1-overexpressing tumors in MUC1-transgenic mice was not accompanied by damage to normal somatic MUC1-positive tissues, even when this involved the infusion of large numbers of clonal cytotoxic T lymphocyte that recognized the immunodominant MUC1 epitope. Although the risk for autoimmune pathology is limited, data indicate that immune tolerance in MUC1-positive subjects restricts the breadth of the MUC1-specific cytotoxic T lymphocyte repertoire that is available for recruitment to immunotherapeutic antitumor responses.